Hole Drilling of High Density Polyethylene using Nd:YAG Pulsed Laser - Taha, Ziad A. (Iraqi Journal of Laser, 2020)
This paper presents the theoretical and experimental results of drilling high densitypolyethylene sheet with thickness of 1 mm using millisecond Nd:YAG pulsed laser. Effects of laserparameters including laser energy, pulse duration and peak power were investigated. To describe andunderstand the mechanism of the drilling process Comsol multiphysics package version 4.3b was used tosimulate the process. Both of the computational and experimental results indicated that the drillingprocess has been carried out successfully and there are two phases introduced in the drilling process,vaporization and melting. Each portion of these phases depend on the laser parameters used in thedrilling process